KARAKTERISTIK ORBIT SATELIT MIKRO DI KETINGGIAN LEO - Nizam Ahmad (Lembaga Penerbangan dan Antariksa Nasional, 2007)
The Micro satellite is commonly placed in Low Earth Orbit (LEO) which has the altitude approximetely about 300-1000 km above surface of the earth. At this altitude, the the orbit of satellite will be influenced by perturbation force from atmospheric drag (Hasting, 1996) and earth oblateness. The understanding of orbit characteristics by studying the space environment where the satellite placed, will give much help in every launch of satellite. In this research, the study conducted by using 6 micro satellite as references with varying altitudes. The simulation result that the placement of satellite in the right position will reduce the effects of those perturbation on the satellite's orbit. It can be seen that all these micro satellites have conducted their mission goals, at least untill this time.